Human Resource Development to Strengthen Competitiveness in the Global Digital Market Era - Dian Arisanti; Kevin Indajang; Ayunda Fatmasari; Muhamad Risal Tawil; Eka Kurnia Saputra (PT FORMOSA CENDEKIA GLOBAL, 2026)
Human resource development is a key pillar in a country's economic transformation. In today's digital and knowledge-based economy, human resources are no longer simply production factors like machines or land, but rather strategic assets that determine global competitiveness. In the digital world, competitive advantage no longer lies in the ownership of physical assets, but rather in data mastery, creativity in problem-solving, and the ability to build trust with consumers worldwide. Human involvement in the global digital market also includes a strategic role in navigating the complexities of varying cultures and regulations in each country. This study aims to provide an analysis of human resource development to strengthen competitiveness in the global digital market era. This analysis uses a qualitative approach from the perspective of a human resources expert. The research findings demonstrate Dave Ulrich and Josh Bersin's understanding that a paradigm shift in human resource management in the global digital market era is no longer merely an option, but a necessity for survival. In the global digital market, the competitiveness of a nation or company is no longer determined by the possession of natural resources, but by the quality of its human capital.